A Meta-analysis on the Relationship between Different Dialysis Modalities and Depression in End-stage Renal Disease Patients - He, Runjun; Tung, Tao-Hsin; Liu, Tingjun; Chien, Ching-Wen (Current Pharmaceutical Design, 2021)
Background: The purpose of this study was to assess the relationship between different dialysis modalities and depression in end-stage renal disease (ESRD) patients. Methods: We searched through the PsycINFO, PubMed, Cochrane Library, EMBASE, and CNKI for all related studies from 1 January 1990 through 30 June 2019 without restriction on language. We selected papers that compared depression levels among patients undergoing hemodialysis and peritoneal dialysis. Two authors independently selected studies, evaluated the quality of included studies, and extracted data according to Newcastle-Ottawa Scale (NOS). A discussion with a third author checked any disagreement to minimize the publication bias. PRISMA guidelines were used as the standards of reporting (PRISMA registration ID is 239172). Results: There was insufficient evidence to prove the relationship between different dialysis modalities and depression (OR: 2.37, 95% CI: 0.88-6.40). We also found no statistical significance between the mean difference of depression level and dialysis modalities (Std mean difference=0.69, 95% CI: -2.09-3.46). Conclusion: The available limited, deficient quality evidence assessed by ROBINS-I does not support an association between depression and dialysis modalities among ESRD patients. Further studies that provide data for different sex and age groups are needed to clarify whether a subgroup of dialysis modalities has a different risk of depression.
Keywords: hemodialysis